Junewangia guizhouensis sp. nov. (Junewangiaceae, Sordariomycetes) from Guizhou Province, China - Gao, Fan; Tan, Tinghong; Wu, Chunfang; Zhao, Ningning; Ma, Jian (Phytotaxa, 2025)
During a survey of hyphomycetous fungi in subtropical regions, two fungal strains were isolated from submerged decaying wood in Guizhou Province, China. Phylogenetic analysis based on a combined dataset of LSU, ITS tef1-α, and rpb2 sequences, coupled with detailed morphological comparisons to other asexual species within Junewangiaceae, supports the introduction of a novel asexual fungal species, Junewangia guizhouensis. A description, illustrations, and phylogenetic analysis results are provided to substantiate its taxonomic placement. Notably, J. guizhouensis is the first species of this genus recorded from Guizhou Province, thereby expanding the known distribution of Junewangia in subtropical aquatic habitats.